ANALISIS KELAYAKAN USAHA PADA BENGKEL BAN MOBIL GRACIA DI KABUPATEN MIMIKA - Andreas Kapitan Teluma; Tri Apriyono (Jurnal Ekonomi dan Bisnis, 2023)
This research aims to determine the business feasibility of the Gracia Car Tire Workshop owned by Mr. Knisius Fobia. The research method used is a descriptive research method, for data collection in this research the methods used are observation, interviews and documentation. The analysis instrument used to determine the business feasibility of the Gracia Car Tire Workshop is an analysis of the financial aspects of Revenue Cost Ratio (R/C Ratio) and Benefit Cost Ratio (B/C Ratio). The results of this research show that the Revenue Cost Ratio at the Gracia Car Tire Repair Business is said to be financially feasible from the Revenue Cost Ratio (R/C Ratio) calculation, while from the Benefit Cost Ratio (B/C Ratio) calculation it is said to be not feasible.